Identification of at Risk Early Grade Children for Dyslexia by Using Prereading Skills in Nepal - Thapa, Krishna Bahadur (Interdisciplinary Research in Education, 2023)
In developing countries like Nepal, dyslexia is still an unfamiliar subject for both public and academic professionals; however it needs to be identified among Nepalese children. The study aimed to (i) identify children at risk for dyslexia which might be considered as a general occurrence of dyslexia among Nepalese primary school children (ii) explore a set of predictive variables in identifying children at risk for dyslexia, and (iii) compare early grade reading skills of children at risk for dyslexia with age and grade-matched control group. Altogether, 554 children from grade 2 through 5 were screened by teachers employing an adapted TSQ and identified 75 children having most difficulty either in reading, spelling, mathematical calculation and behaviour problems by direct assessment administering RSAET and their performance was compared with a control group of 86 peers. The findings revealed that out of 554 children, 13.54% of children were identified at risk for dyslexia at the screening stage, but it was 12.63% verified by direct assessment. The logistic regression analysis classified the risk and control groups with a high accuracy of 91.89% based on reading tasks where prevailing sensitivity of 93.33% and specificity of 91.86% were estimated. Overall findings of the present study indicate that a significant number of early grade children are at-risk for dyslexia in Nepal. The findings are consistent with the prevalence of dyslexia reported by international studies. It highlights a need for full-fledged diagnostic studies that may reveal the actual picture of dyslexia in Nepal and inclusive education.